Pengaruh Promosi, Suasana dan Kualitas Produk Terhadap Keputusan Pembelian Pada Bakerman One Satrio Kuningan - Irgi Ahmad Fauzy; Hariadi Hadisuwarno (CV. Ulil Albab Corp, 2024)
The purpose of this study was to find out and analyze the influence of promotion, atmosphere, and product quality on purchasing decisions at Bakerman One Satrio Kuningan. The data used is primary data collected through questionnaires and processed using SPSS 26 so that the population of all consumers who visit Bakerman One Satrio Kuningan is obtained. The sample amounted to 160 respondents who were selected using the accidental sampling technique. Multiple linear regression analysis was carried out in this study. Classical assumption tests such as normality tests, heteroscedasticity tests, and multicollinearity tests are used to calculate data. The hypothesis test was carried out using the F test and the T test. The results of this study showed that individually promotion, product quality, and service quality had a significant influence on purchase decisions. At the same time, promotion, product quality, and service quality also have an influence on purchasing decisions.